PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO, OPERATIONAL EFFICIENCY RATIO, DAN PROFIT SHARING RATIO TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH - Muhamat Iqbal; Saiful Anwar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
The purpose of this study was to determine the effect of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (OER), and Profit Sharing Ratio (PSR) on Financial Performance in Islamic Commercial Bank. The sample used in this study was nine banks, with the sampling technique using purposive sampling. The analytical methode used is multiple linear regressien with Eviews application tools. The result shows that CAR has no effect on ROA, NPF has a significant negative effect on ROA, FDR has no effcet on ROA, OER has a significant negative effect on ROA, and PSR has no effect on ROA. Simultaneously CAR, NPF, FDR, OER, and PSR affect ROA